2023
DOI: 10.32598/pbr.9.1.1077.1
|View full text |Cite
|
Sign up to set email alerts
|

Polycythemia, Thrombocythemia, and Hyperfibrinogenemia are Associated With Streptozotocin-induced Diabetes and Salt-induced Hypertension in Male Wistar Rats

Abstract: Background: Diabetes mellitus and anaemia are frequently reported to be associated with polycythemia in several studies. Furthermore, some studies also have linked polycythemia with hypertension. However, whether hypertension and diabetes comorbidity had polycythemia/erythrocytosis, thrombocythemia, or hyperfibrinogenemia is unknown. Objectives: This study investigated the incidence of polycythemia, thrombocythemia, and hyperfibrinogenemia in diabetic and hypertensive male Wistar rats. Methods: Thirty male Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…24 Hypoglycaemic activity Induction of diabetes in experimental animals is commonly by chemical method with streptozotocin and alloxan. [56][57][58][59][60][61][62][63][64] It usually involve the destruction of the beta-cells of the Islets of Langerhans in the pancreas with a consequent reduction in synthesis and release of insulin. 56,63 Numerous studies have reported the hypoglycemic activities of S. mombin.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…24 Hypoglycaemic activity Induction of diabetes in experimental animals is commonly by chemical method with streptozotocin and alloxan. [56][57][58][59][60][61][62][63][64] It usually involve the destruction of the beta-cells of the Islets of Langerhans in the pancreas with a consequent reduction in synthesis and release of insulin. 56,63 Numerous studies have reported the hypoglycemic activities of S. mombin.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Acute complications include symptoms such as hypoglycemia, hyperglycemic crises, hyperglycemic hyperosmolar state and diabetes ketoacidosis. Chronic complications include diabetic retinopathy, diabetic nephropathy, diabetic neuropathy, microvascular complications, and haematological abnormalities (Lim, 2014;Nentwich and Ulbig, 2015;Chawla et al, 2016;Okonofua et al, 2021;Getawa and Adane, 2022;Okonofua et al, 2023).…”
Section: Complications Of Diabetes Mellitusmentioning
confidence: 99%